From Digital Collection to Open Access: A Preliminary Study on the Use of Digital Models of Local Culture - Chia-Ling Chang; Chin-Lon Lin; Chi-Hsien Hsu; Yikang Sun (MDPI AG, 2023)
In the past, most cultural content was in a passive state of protection. In recent years, with the popularity of digital printing and the emergence of the concept of open-source sharing, it provides a new idea for cultural preservation. Using cultural elements from the Taitung region as a sample, this study established an open-source database, and completed the production of 60 digital models and the archiving of related materials. Based on the concept of open-source sharing, our research hopes that this database can be applied in more places. Through surveys, it could be concluded that, when the models are designed in parts and are easy to print and display, it is more conductive for the models to be used in promotions and applications. It is expected that each township will have its own localized 3D model database. Through the open-source localized digital model's unrestricted and free features, under the influence of COVID-19, it can also allow people from all over the world who cannot visit these places in person to print the local cultural content remotely, so as to have a three-dimensional under-standing of Taiwanese cultural objects. It is expected that the localized 3D model databases will help promote local cultural improvement and move towards local innovation.